Clinical features of BRCA-positive ovarian cancer - S. Ya. Maximov; E. N. Imyanitov; K. D. Guseinov; T. V. Gorodnova (Сибирский онкологический журнал)
It has been recently proved that cells with impaired BRCA1function demonstrate high sensitivity to platinum-containing derivatives because they are not able to eliminate DNA disorders caused by these agents. Early studies showed that BRCA carriers had better odds of surviving ovarian cancer than do women without these mutations. The purpose of the study was to evaluate clinical significance of BRCA1 mutation carriage in response to chemotherapy as well as to life span in patients with advanced ovarian cancer. Treatment outcomes of 21 patients with advanced ovarian cancer with inherited BRCA1gene mutation, who were treated from January 2000 to January 2008, were analyzed. The control group consisted of 42 (1:2) cases with advanced non-inherited ovarian cancer matched by stage, histological type, age and the extent of primary cytoreductive surgery. All BRCA-positive patients responded to neoadjuvant platinum-containing chemotherapy. In non-inherited ovarian cancer patients, complete response was observed in 36 % (8/8 (100 %) vs 9/25 (36 %); OR 14,8; 95 % CI 1,78–100; p=0,002). In comparison with the control group patients, BRCA-positive patients had higher rates of complete response to the first-line platinum-containing chemotherapy (81 % vs 33,4 %; OR 8,50; 95 % СI 2,52–34,89; p=0,001) and to the second-line chemotherapy (62 % vs 21,4 %; OR 5,96; 95 % СI 1,76–22,50; p=0,004). After the third line chemotherapy, BRCA-positive patients had a tendency to better results (18,8 % vs 5,6 %; p=0,233). A statistically significant improvement in the median relapse-free survival time was observed in patients with BRCA1mutations after the first-line chemotherapy as compared to that observed in the control group patients (20,05 vs 7,21 months; p=0,005). Life span in BRCA-positive patients was significantly longer than in patients with non-inherited ovarian cancer (medium 9,3 years vs 3,4 years; p=0,001).